Edible vegetables as a source of aldose reductase differential inhibitors. (1st October 2017) - Balestri, Francesco; Sorce, Carlo; Moschini, Roberta; Cappiello, Mario; Misuri, Livia; Del Corso, Antonella; Mura, Umberto
Abstract: The hyperactivity of aldose reductase (AR) on glucose in diabetic conditions or on glutathionyl-hydroxynonenal in oxidative stress conditions, the source of cell damage and inflammation, appear to be balanced by the detoxifying action exerted by the enzyme. This detoxification acts on cytotoxic hydrophobic aldehydes deriving from membrane peroxidative processes. This may contribute to the failure in drug development for humans to favorably intervene in diabetic complications and inflammation, despite the specificity and high efficiency of several available aldose reductase inhibitors. This paper presents additional features to a previously proposed approach, on inhibiting the enzyme through molecules able to preferentially inhibit the enzyme depending on the substrate the enzyme is working on. These differential inhibitors (ARDIs) should act on glucose reduction catalyzed by AR without little or no effect on the reduction of alkenals or alkanals. The reasons why AR may be an eligible enzyme for differential inhibition are considered. These mainly refer to the evidence that, although AR is an unspecific enzyme that recognizes different substrates such as aldoses and hydrophobic aldehydes, it nevertheless displays a certain degree of specificity among substrates of the same class. After screening on edible vegetables, indications of the presence of molecules potentially acting as ARDIs are reported. Highlights: Differential inhibitors act on enzymes depending on the nature of the substrate used. Aldose reductase is an enzyme that is susceptible to differential inhibition. Vegetables are a promising source of aldose reductase differential inhibitors.